Trade-offs of water non-market- and market-based management instruments: a Brazilian case study of a sugar and ethanol production area - Alcoforado de Moraes, Márcia M. G.; da Silva, Gerald N. Souza; da Cunha, Marcelo Pereira; Dias, Nilena B. M. (Frontiers in Water, 2025)
Achieving sustainable economic growth while preserving environmental balance demands efficient water allocation—especially in regions like Brazil’s Northeast, where sugarcane expansion may intensify water scarcity. In Pernambuco, one of Brazil’s driest states, irrigated sugarcane production has expanded significantly, effectively exporting “blue water” through ethanol and sugar. Using an integrated economic platform that links optimization models with Brazil’s 2011 regionalized input–output matrix, a hydro-economic diagnosis of four interlinked basins revealed that raw water use is heavily concentrated in the humid region. There, the sugar-ethanol complex—comprising irrigated sugarcane cultivation (sector 3), sugar manufacturing (14), and ethanol production (27)—dominates water consumption. Meanwhile, in the semi-arid region, the Water and Sewage sector (56), classified under Services, is the largest water user. Despite accounting for the majority of raw water use, these sectors contribute relatively little to the region’s economic output. Simulations of market-based and non-market-based instruments under a scarcity scenario were used to evaluate economic reallocation trade-offs. The market-based reallocation slightly increased reservoir storage (851.6 vs. 847.5 Mm3) and boosted economic returns by Brazilian Reais 199 million (BRL 12,892 vs. 12,693), but reduced demand satisfaction levels (75.6% vs. 78.7%), equivalent to approximately 35 Mm3 less water use. This reduction stemmed from an 83.6 Mm3 cut to irrigated agriculture, with reallocations of +19.1 Mm3 to Industry and +28.4 Mm3 to Services, generating returns of +BRL 77.75 million and +130.08 million, respectively. The greatest losses in agriculture occurred in the humid region (−79.99 Mm3; −BRL 9.54 million), while the Services sector in the semi-arid region, especially sector 56, saw the largest gains (+21.27 Mm3; +BRL 83.2 million). Industrial sectors 14 and 27 also benefited, offsetting agricultural losses in the humid zone. However, in the semi-arid region, sugarcane (3) remained inefficient despite its growing share. Although the sugar-ethanol sector consumes ~53% of water, it contributes less than 12% of GDP. These findings highlight the limitations of relying solely on economic instruments to promote efficiency. Effective water governance requires alignment with land-use policies—particularly in water-scarce regions—where unregulated sugarcane expansion may displace more efficient crops and hinder broader development strategies such as urbanization and industrial diversification.